For the sake of argument essays and minority reports - Hitchens, Christopher 1949-2011 (Verso, 1993)
'For the sake of argument, one must never let a euphemism or a false consolation pass uncontested. The truth seldom lies, but when it does lie it lies somewhere in between.'. The global turmoil of the last few years has severely tested every analyst and commentator. Few have written with such insight as Christopher Hitchens about the large events - or with such discernment and with about the small tell-tale signs of a disordered culture. For the Sake of Argument ranges from the political squalor of Washington, as a beleaguered Bush administration seeks desperately to stave off disaster and Clinton prepares for power, to the twilight of Stalinism in Prague; from the Jewish quarter of Damascus in the aftermath of the Gulf War to the embattled barrios of Central America and the imperishable resistance of Saralevo, as a difficult peace is negotiated with ruthless foes. Hitchens' unsparing account of Western realpolitik in the end shows it to rest on delusion as well as deception. The reader will find in these pages outstanding essays on political asassination in America as well as a scathing review of the evisceration of politics by pollsters and spin-doctors. Hitchens' knowledge of the tortuous history of revolutions in the twentieth century helps him to explain both the New York intelligentsia's flirtation with Trotskyism and the frailty of Communist power structures in Eastern Europe. Hitchens' pointed reassessments of Graham Greene, P.G. Wodehouse and C.L.R. James, or his riotous celebration of drinkiny and smoking, display an engaging enthusiasm and an acerbic wit. Equally entertaining is his unsparing rogues' gallery, which gives us unforgettable portraits of the lugubrious 'Dr'Kissinger, the comprehensively reactionary 'Mother' Teresa, the preposterous Paul Johnson and the predictable P.J. O'Rourke.
Keywords: Politique mondiale - 1945-; Éditorialistes - États-Unis; Essays; Politik; États-Unis - Politique et gouvernement - 1945-1989; États-Unis - Politique et gouvernement - 1989-; USA; United States -- Civilization -- 1970-; Aufsatzsammlung